The new learning technologies and their involvement in social exclusion - Peña Lapeira, Camilo (Cooperativismo & Desarrollo, 2016)
Purpose: To provide an overview of how various changes in education have occurred in the presence of information and communications technology (ict), especially in relation to people living with disabilities. Description: With respect to the emergence of ict, knowledge societies have experienced changes in the manner in which such knowledge is appropriated. Unable to access these resources, or not trained in their use, the individual runs the risk of being left out and not be part of sectors of society ranging from personal to business and work relationships. Point of view: It can be affirmed that to the extent that the educational processes of digital literacy are improved for the knowledge and use of ict, the digital divide can be reduced. Conclusions: Education faces the challenge of trying to reduce the digital divide and in turn reduce the social gap created by it, using resources and processes, such as digital literacy, driven by different governments that have allocated as many resources as possible.